Modulation of K+ channels by hydrogen peroxide - Eleazar Vega‐Saenz de Miera; Bernardo Rudy (1992)
External application of hydrogen peroxide (H2O2) was found to inhibit the time-dependent fast inactivation process of three cloned voltage-gated K+ channels expressed in Xenopus oocytes: KShIIIC, KShIIID and HukII. As expected from kinetic models where some channels are still opening while a significant fraction of channels is already inactivated there was a large increase in current magnitude concomitant to inactivation block. The channels otherwise functioned normally. The effects of H2O2 were specific (other cloned voltage-gated K+ channels were not affected), and reversible, the currents returned to normal upon removal of the H2O2. H2O2 is produced during normal metabolism; it could act as a modulator of excitability through effects on K+ channels if effective local concentrations are reached in neuronal regions close to the channel. KShIIIC and KShIIID currents are very similar to an O2-sensitive K+ current present in type I cells of the carotid body which is believed to underlie the modulation of excitability of these cells by changes in arterial O2 pressure. H2O2 has been proposed as an intermediary between O2 and cellular response in the carotid body; our results provide support for this model.